Traçado de tubulação tronco em abastecimento de água rural : um enfoque para escoamento por gravidade - Abarca, Nadya Lizeth Serrano (2018)
One of the causes of water scarcity is the inexistence or precariousness in the service infrastructure, impedes access to liquid, despite the availability of water resources. Rural sectors with a physical environment characterized by population dispersion, marked geographic characteristics and lowincome population, the projects and planning of water supply networks increase quality of life of the population. In this context, the methodology was the definition of a trunk line for rural water supply with gravity flow, called DT-REG. The elaboration of the DT-REG methodology have six steps: (1) obtaining the conventional tracing methodology (MCT); (2) preliminary field test (TPC); (3) obtaining and evaluating the best route (OMT); (4) adaptation and / or insertion of procedure (AIP); (5) obtaining the methodology DT-REG; and, (6) final field test. The result of the evaluation and application of DT-REG showed an index (ID) of more than 4 (1 being "very poor", 4 "reasonable" and 7 "very good"), this indicate that the DT-REG offers a satisfactory behavior. The research indicate that a methodology (based on geographic information systems, hydraulic analysis of the supply network and multiobjective and multicriteria methods), suitable for the definition of trunk pipeline, designed in rural-water-fed SAA can be applied, especially, in cases topographies and like an important social aspects.